Genetic variation and use of provenances of Pinus sylvestris in Spain: application of Allué’s. Phytoclimatic models - Alía, R.; Galera, R.; Agúndez, D.; de Miguel, J.; Notivol, E.; Martín, S. (Forest Systems, 1999)
This paper presents the application of the diagnosis and idoneity methods developped by Allué (1990, 1997) to the study of the relatioship between climate and genetic variation and recomendation for the use of forest reproductive material of Scots pine respectively. Growth phenology of Scots pine provenances, from Spain and Germany, have been studied in a provenance tests located in northern Spain, during two years. Siginificant differences have been found in growth rate and total growth. Differences among Spanish provenances are related to the phytoclimate of origin. Origins from close stands, but different phytoclimate, present different performance in terms of growth phenology. The relationship among genetic variation in growth traits and climate, suggest the use of climatic methods for establishing recommendations for the use of forest reproductive material (FRM) of the species. The Idoneity method is of easy applicability and allow us to differentiate among areas for using the different regions of provenance. A map showing the recommendations of each provenance region in the different regions for FRM use and identification defined in Spain is presented.